1994
DOI: 10.1177/004208169402900406
|View full text |Cite
|
Sign up to set email alerts
|

Bank Representation in Low-Income and Minority Urban Communities

Abstract: The author of this article examines the empirical support for the propositions that bank branches are significantly underrepresented in low-income and minority urban communities and that the problem has worsened in recent years. He tests these propositions with data on bank branch locations from 1970 through 1989 in five cities. The data from two of the cities are consistent with the propositions, but the patterns in the data from the other three cities are either inconsistent or mixed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 2 publications
0
12
0
1
Order By: Relevance
“…Banks began 40. Caskey, John (1992) to offer these accounts partly in response to pressure from unions, which demanded the cards as a way of reducing insecurity in payments. Reportedly, payroll debit cards have been quite successful among both white-and blue-collar workers.…”
Section: B Different Approaches To Broadening Access To Fi Nancial Smentioning
confidence: 99%
“…Banks began 40. Caskey, John (1992) to offer these accounts partly in response to pressure from unions, which demanded the cards as a way of reducing insecurity in payments. Reportedly, payroll debit cards have been quite successful among both white-and blue-collar workers.…”
Section: B Different Approaches To Broadening Access To Fi Nancial Smentioning
confidence: 99%
“…A menudo se cita el famoso artículo de Avery (1991) que analiza la provisión de sucursales bancarias en ciudades, pero las trata como unidades agregadas, es decir, entendiendo las ciudades como puntos (adimensionales), no como áreas. Quizá ejemplos más pertinentes sean: Lord y Wright (1981) para Charlotte, Carolina del Norte; Chang et al (1997) para Nueva York; Topçu (2001) para Estambul; Graves (2003) (para ciudades de Louisiana e Illinois); Caskey (1992) para Atlanta, Denver, San José, Nueva York y Washington); Medina y Núñez (2006), que realizan un estudio similar al de Caskey pero para Bogotá. Para México no se encontraron análisis de este tipo.…”
Section: Firmas Que Se Concentran En El Espacio: Fuerzas De Aglomeraciónunclassified
“…In a study of five cities, Caskey (1992) found that communities with a majority of black and/or Hispanic residents are substantially less likely to have a local bank: indeed, the mean number of banks (including branches) per census tract with a majority of blacks and/or Hispanics is less than half that of "nonminority" tracts. Furthermore, Caskey found some evidence that recent bank closures have disproportionately affected low income and minority communities, and similar results for other cities were found by Leichter (1989).…”
Section: Thatmentioning
confidence: 99%